Aesthetics of Color Rhythm in the Guiding Poster: خليف محمود خليف -معتز عناد غزوان (Al-Academy, 2020)
The idea of rhythm is basically associated with movement, as it is a regular frequency of movement combining between unity and change. Rhythm can be defined as a repetition of a certain element. Rhythm has a major role in the guiding poster which we are today in dire need for in light of escalation of coronavirus pandemic and its dire repercussions on entire international community, as the current research highlights the aesthetics of color rhythm in the guiding poster to confront coronavirus pandemic.The spread of this invisible unknown horror preoccupied the world in different fields of scientific and human knowledge to the extent that man today has started looking for effective medical solutions to put an end to this pandemic on the one hand and looking for preventive methods for this disease on the other hand. Actually, the case has not been easy to deal with these two things. The preventive response has been one of the most prominent challenges to confront this fatal disease. Thus, that matter necessitated for the designer to confront the advance of this disease through the strength of the guiding design especially the poster